(3aGYdjI h JCKjQ HQfGeL hbGFi eYQai Sdhci ai JMSjf HYV GdeJZjQGJ GdfaSjI dOi YjfI ef GdeQGgbjf GdeQJaYjf ai SeGJ GdfeW GdaUGei (B= s Efficacy and effectiveness of a preventive cognitive behavioral program in enhancing some psychological variables among high risk schizotype adolescents - (3CMeO Mfai eMeO eMehO QVhGfs; (3SgjQ agje GdZHGTi (B: s ((3GdbGgQI (B: s (3CMeO Mfai eMeO eMehO QVhGf (B: s, 2017)
(3gOaJ GdOQGSI GdQGgfI Edi bjGS aYGdjI HQfGeL hbGFi eYQai Sdhci(B: (3ef GdOQLI GdKGfjI ai NaV SeGJ GdfeW GdaUGei(B: (3h JMSjf eLehYI ef GdegGQGJ GdGLJeGYjI(B: (3h GdeYQajI(B: (3h OQGSI eOi JCKjQ GdHQfGeL ai QaY eSJhi aYGdjI GdOhQ GdGLJeGYi ddeQGgb ef efXhQ GdhGdOjf(B: (3dOi YjfI ef GdeQJaYjf ai SeGJ GdfeW GdaUGei(B. (3h bO CTGQJ GdfJGFL Ed Cf gfGc aQhb Hjf GdeLehYI GdJLQjHjI h GdeLehYI GdVGHWI ai GdbjGS GdHYOi (B((3HYO JYQVge ddHQfGeL GdhbGFi GdeYQai GdSdhci GdeJYOO GdCHYGO(B) (3Ydi cd ef ebjGSG SeGJ GdfeW GdaUGei GdGjLGHi h GdSdHi(B: (3h cPdc ai ebjGS GdegGQGJ GdGLJeGYjI(B: (3h GNJHGQ GSJQGJjLjGJ Md GdeTcdGJ(B: (3h ebjGS GdeNWWGJ ZjQ GdJhGabjI HGSJKfGA eNWW GdYRdI GdGLJeGYjI h GdGZJQGH(B. (3ceG CTGQJ GdfJGFL GdNGUI HGdeLehYI GdJLQjHjI Ydi hLhO aQhb Hjf GdbjGS GdbHdi h GdbjGS GdHYOi Ydi CZdH eJZjQGJ GdOQGSI ai GJLGg GdbjGS GdHYOi(B: (3h cPdc Hjf GdbjGS GdbHdi h GdbjGS GdJJHYi ai GJLGg GdbjGS GdJJHYis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe Yde GdfaSs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdfeW GdaUGei GdEjLGHis; (3GdfeW GdaUGei GdSdHis; (3SeGJ GdfeW GdaUGeis